Anxiety among COVID-19 Patients during Their Stay in Isolation Ward in a Tertiary Care Center: A Descriptive Cross-sectional Study - Prabhat Rawal (Nepal Medical Association, 2021)
Introduction: Once a patient is diagnosed with COVID-19 infection, they are required to stay in isolation for some period of time without any social interaction whether be at home or in a hospital setting. The fear of contagion, stigmatization of COVID-19, the social isolation and fear of disease complication has undeniably brought lots of stress and other mental health problems among the infected patients. The main aim of this study is to find the prevalence of anxiety among patients staying in the isolation ward of a tertiary care center.